Complementary subicular pathways to the anterior thalamic nuclei and mammillary bodies in the rat and macaque monkey brain. (6th March 2016) - Christiansen, Kat; Dillingham, Christopher M.; Wright, Nicholas F.; Saunders, Richard C.; Vann, Seralynne D.; Aggleton, John P.
Abstract: The origins of the hippocampal (subicular) projections to the anterior thalamic nuclei and mammillary bodies were compared in rats and macaque monkeys using retrograde tracers. These projections form core components of the Papez circuit, which is vital for normal memory. The study revealed a complex pattern of subicular efferents, consistent with the presence of different, parallel information streams, whose segregation appears more marked in the rat brain. In both species, the cells projecting to the mammillary bodies and anterior thalamic nuclei showed laminar separation but also differed along other hippocampal axes. In the rat, these diencephalic inputs showed complementary topographies in the proximal–distal (columnar) plane, consistent with differential involvement in object‐based (proximal subiculum) and context‐based (distal subiculum) information. The medial mammillary inputs, which arose along the anterior–posterior extent of the rat subiculum, favoured the central subiculum (septal hippocampus) and the more proximal subiculum (temporal hippocampus). In contrast, anterior thalamic inputs were largely confined to the dorsal (i.e. septal and intermediate) subiculum, where projections to the anteromedial nucleus favoured the proximal subiculum while those to the anteroventral nucleus predominantly arose in the distal subiculum. In the macaque, the corresponding diencephalic inputs were again distinguished by anterior–posterior topographies, as subicular inputs to the medial mammillary bodies predominantly arose from the posterior hippocampus while subicular inputs to the anteromedial thalamic nucleus predominantly arose from the anterior hippocampus. Unlike the rat, there was no clear evidence of proximal–distal separation as all of these medial diencephalic projections preferentially arose from the more distal subiculum. Abstract : This schematic depicts how the inputs from the subiculum to the anterior thalamic nuclei and mammillary bodies show interleaving topographies. These topographies differ in rats and macaque monkeys.